THE EFFECT OF GREEN BANKING IMPLEMENTATION AND OPERATING COST EFFICIENCY ON FINANCIAL PERFORMANCE AT ISLAMIC COMMERCIAL BANKS IN INDONESIA FOR THE 2019-2023 PERIOD - Karexa Selvia Yundari; Femei Purnamasari; Ahmad Hazas Syarif (JURNAL PROFIT, 2025)
Environmental problems such as climate change and natural disasters are now increasingly frequent. Banking operations that pay less attention to environmental aspects contribute to worsening this situation, because the drive for profit often makes the negative impact of business on the environment ignored. This study aims to analyze the application of green coin rating (GCR) and Operational Cost Efficiency (BOPO) to return on equity (ROE) as an indicator of financial performance at Islamic Commercial Banks in Indonesia for the 2019-2023 Period. The population in this study are all financial reports from 13 BUSs that have been published until 2023. The sample of this study used purposive sampling with a sample of 6 BUS, namely BCA Syariah, Bank Aceh Syariah, Bukopin Syariah, NTB Syariah, Bank Panin Dubai Syariah, and Bank Muamalat, using annual report data and sustainability reports for the 2019-2023 period. The data analysis technique uses panel data regression analysis through the E-Views10 program. The results showed that partially, the application of GCR has a negative and insignificant effect on ROE with a sig value. 0.5845>0.05, while BOPO shows a positive significant effect on ROE with a sig value. 0,0000<0,05. Simultaneously GCR and BOPO have a significant effect with a sig value. 0.000001 <0.05 on ROE at Islamic Commercial Banks in Indonesia for the 2019-2023 Period Keywords: Green Banking, Operating Cost Efficiency, Financial Performance, Islamic Commercial Bank